Evidence Brief: Exploring Models for Pharmacist Prescribing in Primary and Community Care Settings in Ontario - Gauvin, François-Pierre; Lavis, JN; McCarthy, Lisa (My University, 2015)
An assessment of what is known about problems related to pharmacist prescribing, options for addressing these problems, and key implementation considerations. The evidence brief was an input to a stakeholder dialogue on the topic of exploring models for pharmacist prescribing in primary and community care settings in Ontario.
Keywords: models; pharmacist; prescribing; community care; primary; Ontario